Methods of Web Philology: Computer Metadata and Web Archiving in the Primary Source Documents of Contemporary Esotericism. (31st May 2016) - Plaisance, Christopher
Abstract : This article explores the issues surrounding the critical analysis of first generation electronic objects within the context of the study of contemporary esoteric discourse. This is achieved through a detailed case study of Benjamin Rowe's work, A Short Course in Scrying, which is solely exemplified by digital witnesses. This article demonstrates that the critical analysis of these witnesses is only possible by adapting the general methods of textual scholarship to the specific techniques of digital forensics—particularly the analysis of computer metadata and web archives. The resulting method, here termed web philology, is applicable to the critical analysis by the scholar of religion of any primary source documents originating on the web as electronic objects.